(untitled) (مجلة المنصور, 2023)
Geographic information system (GIS) technology can be used for scientific investigations, resource management, and development planning, it is a computer system capable of capturing, storing, analyzing, and displaying geographically referenced information; that is, data identified according to location.The Global Positioning System (GPS) is a satellite-based navigation system made up of a network of 24 satellites placed into orbits, GPS works in any weather conditions and anywhere, GIS is used in this research and is applied to waste and storm water(rainfall)pipelines network in large sector of Mosul university which is described as high population and construction density to be identical sample as urban’s water and wastewater networks, To achieve this research ArcGis was used with aid of updated satellite pictures and Engineering drawing maps, also Gps was used to locate (Manholes) positions with high accuracy, The result was obtained a digital geographical map that can be spatial query about any part of network for monitoring and Maintenance and laying new expansion pipes